Information Literacy As Fetishized Theoretical Category – An Example of Pro-ana Youth Blogs - Siuda, Piotr (Kultura-Społeczeństwo-Edukacja, 2019)
Scientific reflections on information literacy have emphasized that young people must develop information competences related to using the Internet. Among various approaches, in the generic approach, catalogues of competences are constructed and treated as lists of desired behaviours and skills. The article aims to criticize this approach and its characteristic fetishization of theoretical categories; because of fetishization, these catalogues of competences fail to reflect social reality. The article presents the practices of female bloggers of the pro-ana movement: young girls who consider anorexia not a disease but a lifestyle. Using the method of content analysis, the author analysed 561 blog entries on 15 blogs and compared the collected data with a model catalogue of competencies created based on the literature. Perceived from the perspective of the generic approach, female pro-ana bloggers may be considered informationliterate. This implies that this approach is deficient as the pro-ana movement negatively impacts both healthy and ill girls. The analysis indicates that proponents of the generic standpoint should distinguish the so called competent negative uses.